2020
DOI: 10.3390/ijerph17238865
|View full text |Cite
|
Sign up to set email alerts
|

What Motivates Smokers to Switch to ENDS? A Qualitative Study of Perceptions and Use

Abstract: Switching completely from cigarettes to electronic nicotine delivery systems (ENDS) may reduce health risks for addicted smokers. This paper provides information about perceptions and other factors that may influence smokers’ ENDS use and substitution for cigarettes. We conducted 12 online focus groups (N = 61) among smokers who had never tried using ENDS (Never Users, N = 11), currently used both cigarettes and ENDS (Dual Users, N = 21), used but discontinued ENDS (Rejectors, N = 14), and switched completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The ability of noncombustible alternative nicotine-delivery products to provide satisfying effects to adult smokers is central to facilitating switching: subjective satisfaction from ENDS use is associated with continued ENDS use and switching away from smoking (Evans et al 2020 ; Gades et al 2020 ; Goldenson et al 2021c ; Pearson et al 2020 ). In a 1-year longitudinal study of US adult smokers who purchased JUUL, a 1-point increase in subjective ratings of satisfaction at baseline was prospectively associated with 27% greater odds of switching across the follow-up period (Goldenson et al 2021c ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of noncombustible alternative nicotine-delivery products to provide satisfying effects to adult smokers is central to facilitating switching: subjective satisfaction from ENDS use is associated with continued ENDS use and switching away from smoking (Evans et al 2020 ; Gades et al 2020 ; Goldenson et al 2021c ; Pearson et al 2020 ). In a 1-year longitudinal study of US adult smokers who purchased JUUL, a 1-point increase in subjective ratings of satisfaction at baseline was prospectively associated with 27% greater odds of switching across the follow-up period (Goldenson et al 2021c ).…”
Section: Discussionmentioning
confidence: 99%
“…The PK and subjective effect profiles observed herein indicate that the pharmacological abuse liability of all of the JUUL and IQOS products evaluated is lower than that of cigarettes. Given that indices of product appeal commonly used to characterize abuse liability, such as subjective satisfaction, are also important for facilitating switching away from smoking (Evans et al 2020 ; Goldenson et al 2021c ), some degree of abuse liability is deemed necessary for noncombustible products to successfully compete with cigarettes (Abrams et al 2018a , 2018b ; FDA 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…5,28 Indeed, many smokers report the primary reasons for starting use of ENDS were to quit smoking and/or avoid relapse after quitting. [29][30][31][32] Recent evidence suggests that ENDS use can be more successful than NRT use in maintaining smoking cessation when combined with behavioral support. 33 To accomplish long-term transition away from CC use, ENDS must be su ciently satisfying and provide smokers with positive subjective experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of flavors is viewed as an appealing characteristic of ENDS products among both youth/adolescents (Ambrose et al, 2015; Kong et al, 2015; Tsai et al, 2018) and adults (Cheney et al, 2016; Evans et al, 2020; Leventhal et al, 2020; McDonald & Ling, 2015; Patel et al, 2016; Sussman et al, 2014) who use ENDS. The appeal of flavored ENDS is evident among young adults, in particular: A qualitative study of young adults reported that being able to consume a wide variety of e-liquid flavors is a motivation for using ENDS (Cooper et al, 2016).…”
mentioning
confidence: 99%